On the Risk-Adjusted Effective Protection Rate - Eldor, Rafael (The Review of Economics and Statistics, 1984)
Using the assumptions of the Capital Asset Pricing Model this paper presents a measure of the effective protection rate which adjusts for the industry's risk. It is shown that if the tariff on the final good is greater (smaller) than the weighted average tariff on the traded inputs, then the effective protection increases (decreases) as one moves from an industry with low risk (low beta) to an industry with high risk (high beta), holding other things constant. The empirical methodology of the new measure is also provided, as well as several illustrations from U.S. industries.